Risk Factors for Congenital Deafness in Pediatric Patients Who Underwent Otoaccoustic Emission (OAE) and Auditory Brainstem Response (ABR) Examinations in General Hospital Mohammad Hoesin Palembang, Indonesia - Fiona Widyasari; Fani Paulina; Ahmad Hifni; Abla Ghanie; Erial Bahar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Introduction: Congenital deafness is a hearing loss that occurs at birth. Congenital deafness in neonates can be caused by risk factors during pregnancy and during the birth process. The tests carried out for hearing screening for neonates in hospital up to 1 month old are Otoaccoustic Emission (OAE) and Auditory Brainstem Response (ABR) examinations. Objective: Determining the relationship between family history of deafness, syndromes associated with sensorineural hearing loss, TORCH infection and prenatal syphilis, use of ototoxic drugs during pregnancy, prematurity, low birth weight, asphyxia, and hyperbilirubinemia with the incidence of congenital deafness in children Methods: This cross-sectional study was conducted based on medical record datas from children who underwent OAE and ABR examinations at Dr. Mohammad Hoesin Palembang hospital from January 2019 to February 2021. Results: From the 349 children, 180 (51.6%) had bilateral OAE and ABR pass results, 161 (46.1%) had bilateral referrals and 8 (2.3%) children received unilateral refer results. From 122 children with risk factors, 38 (31.1%) children with bilateral passes, 81 (66.4%) children with bilateral referrals and 3 (2.5 %) children with unilateral refer. From 227 children without risk factors, 142 (62.6 %) children with a bilateral pass, 80 (35.2 %) children with bilateral referrals and 5 (2.2%) children with unilateral refer. The most common risk factor was LBW of 41 (11.7%) children. Chi square test and logistic regression analysis results showed a significant relationship between ototoxic drugs during pregnancy and congenital deafness (p = 0.001) with referral results, the value of Odd Ratio (OR) 9.651. Conclusions: There is a significant relationship between risk factors for ototoxic drugs during pregnancy, TORCH and syphilis infection during pregnancy, asphyxia, congenital syndrome, LBWand hyperbilirubinemia with congenital deafness.